CALCULATION RESEARCH OF THE BRAKING EFFICIENCY IMPROVEMENT OF A FREIGHT CAR WITH SEPARATE BRAKING TRUCKS - Donchenko, O. V.; Vodianikov, Yu. Ya.; Safronov, O. M.; Sheleiko, T. V. (Science and Transport Progress, 2009)
The results of design analyses concerning the selection of reduction ratio values are presented. The braking effectiveness and performance of a freight wagon with the separate braking of the bogies meet the normative requirements at these reduction ratio values.